2018
DOI: 10.1016/j.seizure.2018.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Ictal hypoxemia: A systematic review and meta-analysis

Abstract: A B S T R A C TPurpose: To estimate the incidence of ictal hypoxemia (IH) and to identify clinical and study-related factors modulating the estimate. Methods: We searched articles recording concurrent peri-ictal and ictal EEG and Sp02 in adults and children with epilepsy. Studies reporting the total number of seizures recorded and the number of seizures with IH were included in a random-effects meta-analysis. A random-effects meta-regression was used to identify variables affecting study heterogeneity. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…The results of this investigation are consistent with previously published rates of periconvulsive respiratory anomalies (34), postictal leukocytosis (1, 2), periconvulsive endotracheal intubations (30), and postconvulsive CXR findings (19). Moreover, our results revealed a high incidence of anemia in our study population, a finding reminiscent of a previously reported negative correlation between the frequency of epileptic seizures and hemoglobin levels (35).…”
Section: Discussionsupporting
confidence: 92%
“…The results of this investigation are consistent with previously published rates of periconvulsive respiratory anomalies (34), postictal leukocytosis (1, 2), periconvulsive endotracheal intubations (30), and postconvulsive CXR findings (19). Moreover, our results revealed a high incidence of anemia in our study population, a finding reminiscent of a previously reported negative correlation between the frequency of epileptic seizures and hemoglobin levels (35).…”
Section: Discussionsupporting
confidence: 92%
“…Only nonfatal seizures with VLM SD were associated with apnea. We are unaware of descriptions of prolonged apnea during and following nonfatal seizures in other animal models, although in clinical epilepsy hypoxemia is common (Bruno et al, 2018). Other than respiratory effects, nonfatal seizures with brainstem SD could be discriminated from other nonfatal seizures by post-ictal ECoG suppression and increased HRV.…”
Section: Discussionmentioning
confidence: 99%
“…Seizure-related apnea occurs commonly in patients with epilepsy and can result in severe hypoxemia (Nashef et al, 1996;Bruno et al, 2018;Vilella et al, 2019). If prolonged, apnea may be fatal, as such apnea preceded cardiac arrest in rarely monitored cases of "sudden unexpected death in epilepsy" (SUDEP; Ryvlin et al, 2013), a fatal complication of epilepsy affecting patients of all ages (Massey et al, 2014;Devinsky et al, 2016;Harden et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It may be possible to reliably detect seizures by tracking physiological and behavioural variables in a person, for example, their heart rate, movements and electrical conductance of the skin. These might change before, during and after a seizure [7,8]. Remote health technologies may be used, using biosensors that continuously monitor and record signals from the body.…”
Section: Introductionmentioning
confidence: 99%